SIMULATION DESIGN OF AUTOMATIC CONTROL ROOM LIGHTS - Wishnu Prasati; Triyono Triyono, MSC (Jurnal Sistem Komputer, 2000)
To be an efficient use of electricity doperlukan a tool that can control and regulate the use of electric current by way of determining when power consumption is required and when the timing is not needed is to add a timer or a timer on the apparatus. For this purpose appropriate media to be utilized is to use the computer as a tool in the media deemed appropriate and simplify the operation of the simulation control room lighting that will be discussed. To apply in accordance with the desired computer, software or software here also play an important role. High-level programming language with ease in implementation problems. Programming language to be used is Borland Delphi 3.0 programming language similar to Pascal. The software will be created is expected to control and regulate or pewaktuyang Timer can be set manually on the computer and then apply it to the interface and circuit simulation equipment room has been created.